Telaah Kendala Penerapan Pengembangan Ekonomi Lokal: Pragmatisme Dalam Praktek Pendekatan Pel - Ery Supriyadi R (Journal of Regional and City Planning, 2007)
Local Economic Development (LED) approach is an alternative for development country like Indonesia. Strategy, programe, and activity of LED have strength besides its weaknesses of the implementation. LED have five fundamental constrain in its implementation, such as politics, strategics, expertises, finance, and operational.  All of these should be concerned on its implementation, not only in formulating but also in implementing and controlling of LED programes. Some important weakness at implementation of LED are needs of thought and action commitment such as priority scale tasks, bridging gap of idea and activity, elimination gap of administrators and politician, adjustment of internal institution, and sustainability of activity. Weaknesses have to be identified from three aspects as strategic and initiatives aspect, institutional aspect, planning and implementing aspect of LED. Strength of LED that have to concerned as LED implementation signal such as policy reformation, encourage economical cooperation that profitable for backward and forward linkages, urban and rural linkage, added value of comodity and bussiness diversification. Besides, LED emerge strategic vision of economic development, role of coordination, private participation, regional perspective, creativity, and political commitment for economic development.